2018
DOI: 10.1111/cen.13909
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin therapy in hypopituitarism: Challenges and opportunities

Abstract: Summary Patients with hypopituitarism display impaired quality of life and excess morbidity and mortality, despite apparently optimal pituitary hormone replacement. Oxytocin is a neuropeptide synthesized in the anterior hypothalamus which plays an important role in controlling social and emotional behaviour, body weight and metabolism. Recent studies have suggested that a deficiency of oxytocin may be evident in patients with hypopituitarism and craniopharyngioma, and that this may be associated with deficits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Oxytocin is a neuropeptide hormone synthesized in the anterior pituitary and stored and released from the posterior pituitary. Oxytocin stimulates uterine contraction, cervical ripening, and dilation, and promotes clotting in the postpartum period [ 6 ]. Oxytocin is closely related to vasopressin in molecular structure and widely used for induction or augmentation of labor, prevention, and management of postpartum hemorrhage and is used as an adjunctive treatment of abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin is a neuropeptide hormone synthesized in the anterior pituitary and stored and released from the posterior pituitary. Oxytocin stimulates uterine contraction, cervical ripening, and dilation, and promotes clotting in the postpartum period [ 6 ]. Oxytocin is closely related to vasopressin in molecular structure and widely used for induction or augmentation of labor, prevention, and management of postpartum hemorrhage and is used as an adjunctive treatment of abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the need for replacement treatment remains mainly theoretical, although a cross‐sectional study demonstrated that low oxytocin levels were associated with lower bone mass density and less favourable hip geometry, 152 as well as with cognitive impairment. Preliminary results provide some evidence of potential benefits of oxytocin therapy with respect to improving these deficits and accompanying metabolic disturbances 153,154 . Oxytocin is currently administered as an i.v.…”
Section: Treatmentmentioning
confidence: 98%
“…Preliminary results provide some evidence of potential benefits of oxytocin therapy with respect to improving these deficits and accompanying metabolic disturbances. 153,154 Oxytocin is currently administered as an i.v. preparation to induce or augment…”
Section: CDImentioning
confidence: 99%
“…It is one of the few hormones that work by the positive feedback mechanism. Its functions include stimulation of uterine contractions as well as stimulation of the myoepithelial cells in the female breast causing milk expression [ 1 ]. In clinical practice, exogenous oxytocin is approved for use in the antepartum period to strengthen uterine contractions, to facilitate vaginal delivery of the fetus.…”
Section: Introductionmentioning
confidence: 99%